Energy-based approach to the assessment of traffic flow - Volodymyr Polishuk; Stanislav Popov; Inna Vyhovska; Serhii Yanishevskiy; Liudmyla Nahrebelna (Transport Technologies)
This article focuses on modeling vehicle acceleration noise in different road conditions, emphasizing urban, highway, and rural roads in Ukraine. Acceleration noise, which refers to the fluctuations in a vehicle's acceleration, is a critical factor in vehicle safety, fuel efficiency, and driving comfort. The research aims to improve current vehicle dynamics models by integrating multi-body dynamics and machine learning algorithms, allowing for more precise predictions of acceleration variability in real-time.